Evolutionary transgenomics: prospects and challenges - Correa, Raul; Baum, David A. (Frontiers in Plant Science, 2015)
Many advances in our understanding of the genetic basis of species differences have arisen from transformation experiments, which allow us to study the effect of genes from one species (the donor) when placed in the genetic background of another species (the recipient). Such interspecies transformation experiments are usually focused on candidate genes – genes that, based on work in model systems, are suspected to be responsible for certain phenotypic differences between the donor and recipient species. We suggest that the high efficiency of transformation in a few plant species, most notably Arabidopsis thaliana, combined with the small size of typical plant genes and their cis-regulatory regions allow implementation of a screening strategy that does not depend upon a priori candidate gene identification. This approach, transgenomics, entails moving many large genomic inserts of a donor species into the wild type background of a recipient species and then screening for dominant phenotypic effects. As a proof of concept, we recently conducted a transgenomic screen that analyzed more than 1100 random, large genomic inserts of the Alabama gladecress Leavenworthia alabamica for dominant phenotypic effects in the A. thaliana background. This screen identified one insert that shortens fruit and decreases A. thaliana fertility. In this paper we discuss the principles of transgenomic screens and suggest methods to help minimize the frequencies of false positive and false negative results. We argue that, because transgenomics avoids committing in advance to candidate genes it has the potential to help us identify truly novel genes or cryptic functions of known genes. Given the valuable knowledge that is likely to be gained, we believe the time is ripe for the plant evolutionary community to invest in transgenomic screens, at least in the mustard family Brassicaceae where many species are amenable to efficient transformation.